Abnormal Gray Matter Structural Covariance Networks in Children With Bilateral Cerebral Palsy - Liu, Heng; Jiang, Haoxiang; Bi, Wenchuan; Huang, Bingsheng; Li, Xianjun; Wang, Miaomiao; Wang, Xiaoyu; Zhao, Huifang; Cheng, Yannan; Tao, Xingxing; Liu, Congcong; Huang, Ting; et al. (Frontiers in Human Neuroscience, 2019)
Bilateral cerebral palsy (BCP) is a common movement disorder in children, which often results in lifelong motor disability. One main symptom of BCP shows the limitations of hand function in everyday activities and participation restrictions. However, the neuroanatomical mechanisms for the manual ability are poorly understood. Recent advances in the understanding of cerebral palsy include the development of coordinated pairwise gray matter, which is important for sensorimotor integration, and cognitive development. Here, in our study, neuroimaging with network analysis was employed to evaluate the changes of structural covariance networks (SCNs) in Chinese BCP children. We aimed to elucidate the alteration of SCNs based on cortical thickness (CT), and to reveal the relationship of CT and hand function in the participants with BCP. SCNs were constructed using covariance between regional CT, which was acquired from T1-weighted images of 19 children with BCP and 19 demographically matched healthy controls (HCs). Compared with HCs, BCP children showed increased CT in several regions involving the bilateral areas (lateraloccipital, lingual, and fusiform) and right areas (cuneus, pericalcarine, inferiortemporal, middletemporal, superiortemporal, and insula). Decreased CT was found in the left superior temporal and right superior parietal cortices. Global network analyses revealed significantly decreased normalized clustering and small-worldness in the BCP network. The area under the curve (AUC) of global network measures varied slightly between the BCP and HCs networks. The resistance of the both SCNs to the target and random attack showed no significant difference. Also, the BCP foci (right superior temporal and subtemporal cortex) showed a significantly negative correlation between the CT and manual ability. In this work, we identified the CT-based SCNs changes in Chinese children with BCP. The abnormal topological organization of SCNs was revealed, indicating abnormal CT, incongruous development of structural wiring, destructive nodal profiles of betweenness, and moved hub distribution in BCP children. This may provide a neuroanatomical hallmark of BCP in the developing brain. Therefore, our results may not only reflect neurodevelopmental aberrations but also compensatory mechanisms.